Design of blockchain based security schemes for vehicle communication networks - Yong, Yong Xing (2019)
The development of Vehicular Network (VANET) has brought many advantages to the transportation system. However, it is prone to security threats. Without proper protection, VANET might bring more harm than good to the transport system. Therefore, in this project, the threats of VANET will be identified and studies regarding Blockchain will be studied. The objective of this project is to design a Blockchain based security schemes for VANET. Eventually, Vehicular Network with Blockchain (VNB) provided by Ethereum was developed. Testing was conducted on the Graphical User Interface where it will generate a random number of vehicles for the user to choose from. Once the vehicle is chosen, VNB will then authenticate the vehicle with Blockchain and Trusted Authority (TA). VNB should only allow the legitimate vehicle with Blockchain account to start using Vehicle Communication (VC). For vehicles that did not pass the authentication process, error messages will be shown to the user on the Graphical User Interface. It was concluded that VNB was able to classify the type of vehicles correctly and only allowed the authenticated vehicle to communication in VANET. These preliminary test results have successfully proved that Blockchain can be the technology to resolve the security issue in VANET.